2022
DOI: 10.1093/cid/ciac687
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Use of Oral Antiviral Agents on the Risk of Hospitalization in Community Coronavirus Disease 2019 Patients (COVID-19)

Abstract: Background We examined the effectiveness of molnupiravir and nirmatrelvir/ritonavir in reducing hospitalization and deaths in a real-world cohort of non-hospitalized COVID-19 patients. Methods This was a territory-wide retrospective cohort study in Hong Kong. Non-hospitalized COVID-19 patients who attended designated outpatient clinics between 16 February and 31 March 2022 were identified. Patients hospitalized on the day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(135 citation statements)
references
References 19 publications
5
129
1
Order By: Relevance
“…We have confirmed these favourable findings also in the non-vaccinated population and in patients with two doses of anti-SARS-CoV-2 vaccine. Favourable outcomes in our results are in line with real-life data published by other centres [ 10 , 11 , 17 , 18 ], despite that most of the patients considered in other studies were treated from the beginning as outpatients. Patients’ characteristics who died in the study populations were reported in Table 5 : we found high comorbid patients, with high Charlson comorbidity index who died for complications other than COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…We have confirmed these favourable findings also in the non-vaccinated population and in patients with two doses of anti-SARS-CoV-2 vaccine. Favourable outcomes in our results are in line with real-life data published by other centres [ 10 , 11 , 17 , 18 ], despite that most of the patients considered in other studies were treated from the beginning as outpatients. Patients’ characteristics who died in the study populations were reported in Table 5 : we found high comorbid patients, with high Charlson comorbidity index who died for complications other than COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Another study of the real-world effectiveness of molnupiravir from Hong Kong with a comparable population size also reported an interaction between the age group (above or below 65) and molnupiravir treatment. Moreover, this study reported a signi cantly higher risk of hospitalization among younger patients and no bene t in older patients (11).…”
Section: Discussionmentioning
confidence: 53%
“…Several studies have aimed to assess effectiveness of nirmatrelvir-ritonavir under real-world conditions of use in Israel, Hong Kong, and the United States, each yielding lower effectiveness estimates than those observed in the EPIC-HR trial. [7][8][9][10][11][12] Because the perceived risk for a patient to progress to severe disease endpoints likely factors into clinical decision-making around nirmatrelvir-ritonavir prescribing and patients' adherence to treatment, controlling for potential differences in clinical status among patients who receive or do not receive treatment is of key importance to causal inference. However, symptoms data were lacking in prior observational studies from all [7][8][9][10][11] or most 12 patients analyzed, hindering the possibility to control for differences in patients' clinical stage or disease severity potentially associated with treatment receipt.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Because the perceived risk for a patient to progress to severe disease endpoints likely factors into clinical decision-making around nirmatrelvir-ritonavir prescribing and patients' adherence to treatment, controlling for potential differences in clinical status among patients who receive or do not receive treatment is of key importance to causal inference. However, symptoms data were lacking in prior observational studies from all [7][8][9][10][11] or most 12 patients analyzed, hindering the possibility to control for differences in patients' clinical stage or disease severity potentially associated with treatment receipt. Our sensitivity analyses allowing for relaxed matches with respect to patients' symptomatic status identified progressively lower estimates of treatment effectiveness with looser matching on time from symptoms to testing, and without matching on presence or timing of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation